Thermal Properties of the Foundry Sand Mould Material Bonded with Resol Type Resin - Piwowarski, G.; Woźniak, F.; Roszko, A.; Fornalik-Wajs, E. (Archives of Foundry Engineering, 2026)
This study presents a comprehensive analysis of the thermophysical properties of a casting mould based on BK 50 quartz sand and a resol-type phenol-formaldehyde resin. The investigation combines classical laboratory measurements using Differential Scanning Calorimetry (DSC) with in-situ temperature field recording inside a foundry mold during the solidification of a copper plate casting. Based on specific heat capacity data and readings from seven thermocouples, temperature-dependent values of thermal diffusivity (a), heat capacity (b), and thermal conductivity (λ) were determined. The results indicate a low thermal conductivity of the tested material and a strong temperature dependence of its thermophysical properties. A significant influence of residual moisture was observed during the initial heat exchange phase, manifesting as disturbances in the heating curves around 100 °C. The adopted methodology enabled a realistic mapping of thermal conditions during solidification and confirmed the stable course of the process. The identified thermophysical coefficients characterize the material and are crucial for providing accurate input parameters in numerical simulations of casting processes. Furthermore, they support the informed selection of molding materials in industrial applications, contributing to more reliable simulation outcomes and improved process design, material selection, and final casting quality. The findings validate the integration of laboratory measurements with in-situ analysis and point to the necessity of further research involving various binders, sand grain size distributions, and elevated pouring temperatures.